Prevalence of sexually transmitted infections and bacterial vaginosis among lesbian women: systematic review and recommendations to improve care - Soligo Takemoto, Maira Libertad; Menezes, Mariane de Oliveira; Andreucci Polido, Carla Betina; Santos, Debora de Souza; Leonello, Valeria Marli; Magalhaes, Claudia Garcia [UNESP]; Cirelli, Jessica Fernandes; Knobel, Roxana (Cadernos Saude Publica, 2019)
Our aim was to systematically review data about the risk of sexually transmitted infections (STI) and bacterial vaginosis among lesbian women and to suggest strategies to improve prevention, diagnosis and treatment. A search strategy for lesbian, STI and bacterial vaginosis was applied to PubMed, LILACS and BDENF databases. Of 387 unique references retrieved, 22 fulfilled the inclusion criteria (cross-sectional studies reporting prevalence for 8 STIs/bacterial vaginosis and history of a STI). The most frequent infection reported was bacterial vaginosis, and none study reported data on hepatitis B. A wide range of prevalence was observed for most infections. In terms of risk factors, the number of sexual partners, the past or current smoking, a history of forced sex and sexual stigma seem to increase the risk of STI and bacterial vaginosis. The findings of this review are discussed considering guidelines directly addressing the LGBT community's health and relevant studies investigating both safe sexual practices and the intricate relationship between LGBT people and their care providers. A set of recommendations to improve preventive care for lesbian women is proposed. Affirming that little is known about the extent of STIs and bacterial vaginosis transmission in female-to-female sexual activities or about the risk factors for STI and bacterial vaginosis among lesbian women is reasonable. In fact, the overall quality of the studies was low or very low with significant uncertainty around their findings. However, we consider that the available knowledge indicates some paths to be followed by care providers and policy decision-makers to improve their actions towards better sexual health of lesbian women.
Keywords: Sexually Transmitted Diseases; Bacterial Vaginosis; Female Homosexuality; Health Policy